Спектральні густини потужності як функція частоти для різних кольорів шуму (цифрова система генерації рожевого шуму) - Пупловський, Д. С. (ХНУРЕ, 2023)
This paper investigates the power spectral density of different noise colors using a digital pink noise generation system. Power spectral density is an important characteristic for describing the spectral composition of a signal, which provides information on the distribution of signal energy depending on the frequency. A comparative analysis of the spectra of different colors of noise was carried out, which allows us to understand how they affect the power spectral density in different ways. This study can be useful for various fields of science and technology where different types of noise are used, for example, in audio engineering, telecommunications and other industries.
Keywords: генерація рожевого шуму